Wind Energy System based on Buck-Boost Controller - Ansari Nabila Alravi Arif Husain; R. K. Agrawal (Journal of Power Electronics and Devices, 2016)
In this edge most of the countries are facing energy related problem, therefore, researchers are now try to find such a system which should not create any environment issues. In nature there is various non-conventional resources use for the generation of electricity such as water, sunlight, geothermal energy. But there is disadvantage of solar energy is that we cannot generate power using solar energy in rainy season and in night time. Whereas, wind energy is very safe clean and natural source to generate energy. If the wind speed is low, the output voltage will not be up to that level to charge the battery as it is lower than the required charging voltage of the battery. This reason reduces the overall performance efficiency of the Wind Machine to 20%. This suggested idea and design will enable effective utilization of wind machine. The buck boost converter bucks/reduces this high voltage to the required battery charging voltage and if wind machine output voltage is low then converter will boost the voltage to charge the battery, thereby protecting the battery from over charging. Thus, the effective utilization of the wind machine has been achieved by the use of the proposed Buck Boost Controller.